Application of Arbuscular Mycorrhizal Fungi in Vineyards: Water and Biotic Stress Under a Climate Change Scenario: New Challenge for Chilean Grapevine Crop - Aguilera, Paula; Ortiz, Nancy; Becerra, Ninozhka; Turrini, Alessandra; Gaínza-Cortés, Felipe; Silva-Flores, Patricia; Aguilar-Paredes, Ana; Romero, Juan Karlo; Jorquera-Fontena, Emilio; Mora, María de La Luz; Borie, Fernando (Frontiers in Microbiology, 2022)
Abstract The crop of Vitis vinifera (L.) is of great economic importance, as Chile is one of the main wine producing countries, reaching a vineyard area of 145,000 ha. Vine crop is usually very sensitive to local condition changes and agronomic practices, therefore, strategies to counteract future expected decrease in water for agricultural irrigation, temperature increase, extreme water stress (abiotic stress), as well as the increase in pathogenic diseases (biotic stress) related to climate change, will be of vital importance for this crop. Studies carried out in recent years have suggested that arbuscular mycorrhizal fungi (AMF) can provide key ecosystem services to host plants, such as water uptake implementation enhanced absorption of nutrients such as P and N, key factors for improving the nutritional status of the vine. AMF use in viticulture will contribute also to the sustainable agronomic management, and to the bioprotection against pathogens. Here, we will present 1) the current status of grapevines in Chile; 2) the main problems in grapevines, related to water stress and associated with climate change; 3) the importance of AMF to face water stress and pathogens, and 4) the application of AMF as a biotechnological and sustainable tool in vineyards.